FORMULASI MASKER GEL PEEL-OFF EKSTRAK ETANOL 96% AMPAS TEH HIJAU (Camellia sinensis Linn.) [FORMULATION OF A PEEL-OFF GEL MASK USING A 96% ETHANOL EXTRACT FROM GREEN TEA DREGS (Camellia sinensis Linn.)] - Jessica Trisina; Riskianto Riskianto; Feronia Reni Cyrena Santoso; Saur Barita Romauli Nainggolan (FaST : Jurnal Sains dan Teknologi, 2022)
Green tea (Camellia sinensis Linn.) is widely consumed in Indonesia, but the dregs which are waste have not been utilized optimally. A previous study revealed that a 96% ethanol extract from green tea dregs produces antibacterial activity against Staphylococcus aureus and Escherichia coli. Therefore, the purpose of this study was to increase the utilization of green tea dregs in cosmetic products in the form of a peel-off gel mask with an active ingredient of 96% ethanol extract from green tea dregs. The green tea dregs extract was made by the maceration method with 96% ethanol as the solvent. The peel-off gel mask was made in three formulas with different variations in the gel base, namely PVA 10% and HPMC 2%; PVA 8% and HPMC 3%; PVA 5% and HPMC 4%. The peel-off gel mask was produced, then it was evaluated by an organoleptic test, pH test, homogeneity test, spreadability test, and dry time test. The peel-off gel was stored for 10 days at two different temperatures, namely room temperature, and refrigerator temperature. The evaluation result was obtained that all three formulations of the peel-off gel mask met the criteria for good gel. However, after 10 days of storage at both storage temperatures, there was a change in the color of the three formulas. The Formula 3 (PVA 5% and HPMC 4%) stored at refrigerator temperature also showed an increment in dry time result. These results indicate the instability of the peel-off gel mask during storage. The peel-off gel mask formula from green tea dregs meets the requirements of gel preparations.Bahasa Indonesia Abstract:Teh hijau (Camellia sinensis Linn.) banyak dikonsumsi di Indonesia, namun ampas yang merupakan limbahnya belum dimanfaatkan secara optimal. Pada penelitian sebelumnya ekstrak etanol 96% ampas teh hijau memiliki aktivitas antibakteri pada Staphylococcus aureus and Escherichia coli. Oleh karena itu, tujuan dari penelitian ini adalah untuk meningkatkan pemanfaatan ampas teh hijau menjadi produk kosmetika berupa masker gel peel-off dengan bahan aktif ekstrak etanol 96% ampas teh hijau. Ekstrak ampas teh hijau dibuat dengan metode maserasi dengan pelarut etanol 96%. Masker gel peel-off dibuat dalam tiga formula dengan variasi basis gel yang berbeda, yaitu PVA 10% dan HPMC 2%; PVA 8% dan HPMC 3%; PVA 5% dan HPMC 4%. Masker gel peel off yang dihasilkan kemudian dievaluasi dengan uji organoleptik, uji pH, uji homogenitas, uji daya sebar, dan uji waktu kering. Gel peel off disimpan selama 10 hari pada dua suhu yang berbeda yaitu suhu ruang dan suhu lemari es. Hasil evaluasi diperoleh bahwa ketiga formulasi masker gel peel-off memenuhi kriteria sediaan gel yang baik. Namun setelah 10 hari penyimpanan pada kedua suhu penyimpanan, terjadi perubahan warna pada ketiga formula. Formula 3 (PVA 5% dan HPMC 4%) yang disimpan pada suhu lemari es juga menunjukkan peningkatan hasil waktu kering. Hasil ini menunjukkan ketidakstabilan sediaan selama penyimpanan.